PERENCANAAN PEMBELAJARAN BERKARAKTER PADA MATA PELAJARAN AGAMA ISLAM DI SMAN 7 KOTA BANJARMASIN - Mizani, Hilmi (Tarbiyah, 2014)
This study aims to know the character basedinstructional planning on the subject of Islamic Education in SMAN 7 Banjarmasin. This research is a field research with qualitative approach and used descriptive method. The data in this research are collected through interview, documentary, and observation. The study found out that the Islamic educationteacher at the SMAN 7 Banjarmasin prepares the instructional planningwhich consists of annual program, semester program, syllabus, and lesson plan. The characters that must be taught have been stated explicitlyin both syllabus and lesson plan for class XI and class XII, but not in in class X. The characters which will betaughtatthe SMAN 7 Banjarmasin and are in both the syllabus and the lesson plan are: religious, honest, tolerance, discipline, hard work, independent, democratic, curiousity, the spirit of nationalism, patriotism, respect for achievement, friendship, love peace, love reading, environmental care, social care, and responsibility.Keyword : Instruction, planned, and character